Contrasting roles for BMP-4 and ventromorphins (BMP agonists) in TGFβ-induced lens EMT. (May 2021) - Shu, Daisy Y.; Ng, Kevin; Wishart, Tayler F.L.; Chui, Juanita; Lundmark, Malin; Flokis, Mary; Lovicu, Frank J.
Abstract: Transforming growth factor beta (TGFβ) and bone morphogenetic protein (BMP) signaling play opposing roles in epithelial-mesenchymal transition (EMT) of lens epithelial cells, a cellular process integral to the pathogenesis of fibrotic cataract. We previously showed that BMP-7-induced Smad1/5 signaling blocks TGFβ-induced Smad2/3-signaling and EMT in rat lens epithelial cell explants. To further explore the antagonistic role of BMPs on TGFβ-signaling, we tested the capability of BMP-4 or newly described BMP agonists, ventromorphins, in blocking TGFβ-induced lens EMT. Primary rat lens epithelial explants were treated with exogenous TGFβ2 alone, or in combination with BMP-4 or ventromorphins. Treatment with TGFβ2 induced lens epithelial cells to undergo EMT and transdifferentiate into myofibroblastic cells with upregulated α-SMA and nuclear translocation of Smad2/3 immunofluorescence. BMP-4 was able to suppress this EMT without blocking TGFβ2-nuclear translocation of Smad2/3. In contrast, the BMP agonists, ventromorphins, were unable to block TGFβ2-induced EMT, despite a transient and early ability to significantly reduce TGFβ2-induced nuclear translocation of Smad2/3. This intriguing disparity highlights new complexities in the responsiveness of the lens to differing BMP-related signaling. Further research is required to better understand the antagonistic relationship between TGFβ and BMPs in lens EMT leading to cataract. Highlights: BMP-4 is effective at blocking TGFβ2-induced EMT in lens epithelial explants. Ventromorphins 1 or 2 (BMP agonists), do not block TGFβ2-induced lens EMT. BMP-4 does not impact TGFβ2-induced Smad2/3 nuclear translocation in LECs. The antagonistic relationship between TGFβ and BMPs in lens EMT is complex.